2005
DOI: 10.1017/s0022029905000828
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating capacity of kefir

Abstract: Kefir is a fermented milk produced by the action of lactic acid bacteria, yeasts and acetic acid bacteria, trapped in a complex matrix of polysaccharides and proteins. Beyond its inherent high nutritional value as a source of proteins and calcium, kefir has a long tradition of being regarded as good for health in countries where it is a staple in the diet. However, published human or animal feeding trials to substantiate this view are not numerous. The aim of this work was to determine the immunomodulating cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
139
0
15

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(164 citation statements)
references
References 42 publications
10
139
0
15
Order By: Relevance
“…In this study, a significant increase in the number of IgG+ cells was observed in mice consuming pasteuri zed kefir. This increase in intestinal IgG had no detrimental effects in the gut, since no tissue damage or alteration of int estinal structures had been observed, as revealed by previous haematoxilineosin studies (22). Macrophages are considered the first line of defen se in the immun e response to foreign invaders.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…In this study, a significant increase in the number of IgG+ cells was observed in mice consuming pasteuri zed kefir. This increase in intestinal IgG had no detrimental effects in the gut, since no tissue damage or alteration of int estinal structures had been observed, as revealed by previous haematoxilineosin studies (22). Macrophages are considered the first line of defen se in the immun e response to foreign invaders.…”
Section: Discussionmentioning
confidence: 79%
“…Kefir containing viable bacteria was able to achieve a similar effect on the number of IgA+ cells as did pasteurize d kefir, even though the former had been admnistered lO times less concentrated than the latter. According to the number of IgA+ and IgG+ cells in the small intestine lamina propria and to haematoxi lin-eosin studies , 2 days of feeding with kefir diluted 1/100 and 5 days of feeding with pasteurized kefir diluted 1/10 were the conditions able to best modulate the intestinal mucosal immune reponse (22). The main function of secretory IgA in the gut is to exert immune exclusion by intimate cooperation with the innate non-specific defence mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations